Epicuro e o epicurismo: a filosofia enquanto exercício para o bem viver - Santos, Rogério Lopes dos (2015)
This dissertation aims to make clear just how Epicurus developed his arguments by pointing ataraxia as the purpose of life. Few works of Epicurus remained: three letters (Letter to Herodotus, Letter to Pythocles, Letter to Menoeceus), each one addressed to a disciple in particular, as well as some maxims (Sovereign Maxims and Vatican Sayings) where his tetraphármakon a set four maxims that are the foundation of his Philosophy are. For Epicurus, the beginning (arché) and the end (télos) of all human action would correspond to a physical and mental state of imperturbability. This condition desired by Epicurus was expressed by the Greek concept of ataraxia (ἀταραξία), also present among the stoics and skeptics. However, the means from which ataraxia would be achieved differed among these three philosophies. To Epicurus, in particular, ataraxia would only be possible to the extent that the sources of error were dissolved, the reason why he strove to clarify: (a) the natural mechanisms through which humans relate to the world; (b) the principles of Nature (phýsis), the ignorance of which resulted in the belief of divine beings who punish the human race. It is with research about man and Nature, in order to reach ataraxia, that arise considerations of Epicurus about religion, about fear of death and about pleasure. This shows the unity of Epicurus' Philosophy. Concerned about the cultural condition, political and religious man, he went from Physics to the Ethics, in doing so, he went, through different paths of knowledge.